North Carolina's Community Health Worker Initiative - Jeanne Milliken Bonds; James H Johnson; Elizabeth Ordonez (Archives of Community Medicine and Public Health - Peertechz Publications, 2022)
Community Health Workers support frontline public health professionals during times of public health pandemics by providing communities with trusted messengers that are a support system and liaison to medical and social services. North Carolina deployed Community Health Workers during the COVID-19 pandemic using funding under the Patient Protection and Affordable Care Act with success. We offer recommendations for a more robust program going forward using what was learned during the pandemic.